A Comprehensive Analysis of Plasmonics-Based GaAs MSM-Photodetector for High Bandwidth-Product Responsivity. (24th September 2013) - Das, Narottam; Fadakar Masouleh, Farzaneh; Mashayekhi, Hamid Reza
Abstract : A detailed numerical study of subwavelength nanogratings behavior to enhance the light absorption characteristics in plasmonic-based metal-semiconductor-metal photodetectors (MSM-PDs) is performed by implementation of 2D finite-difference time-domain (FDTD) algorithm. Due to the structure design and changes in the device physical parameters, various devices with different geometries are simulated and compared. Parameters like nano-grating height and duty cycle (DC) are optimized for rectangular and taper subwavelength metal nanogratings on GaAs substrate and their impact on light absorption below the diffraction limits are confirmed. The calculated light enhancement is 32.7-times for an optimized device in comparison with a conventional MSM-PD. This enhancement is attributed to the plasmonic effects in the near-field region.